Adrian Grant's pioneering use of evidence synthesis in perinatal medicine, 1980-1992 - Iain Chalmers (BMC, 2018)
Abstract Systematic reviews of existing research are needed to help reduce the enormous amount of wasted resources in biomedical research. Whether already available or needed but unavailable, systematic reviews are a key element in prioritising questions for new research, and for informing the design of additional studies. One of the most important of Adrian Grant's many contributions was to recognise this a decade before it began to become more widely accepted. In this sphere, as well as in many others, he was a real pioneer.